Measuring Effective Tax Rates on Human Capital: Methodology and an Application to Canada - Kirk A. Collins; James Davies (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper examines the impacts of a wide range of tax provisions on the incentive to invest in human capital, and shows how these effects can be quantified using effective tax rates, or ETRs. For individuals with median earnings, ETRs on the human capital formed in first-degree university study are sizeable, although not as large as those estimated by previous authors for physical capital in Canada. When the expenditure side and its direct subsidies are also taken into account, the net effective tax rate on human capital becomes negative. The taxation of human capital is far from uniform. ETRs vary by income level, gender, part-time vs. full-time study, whether students have loans, number of dependants, and use of RESPs. The most significant differences are those related to income level. Workers at higher percentile levels of the earnings distribution throughout life may face ETRs three times as high as those for low-income workers - a result of our progressive income tax system.
Keywords: 330